Al-Qur'an Sebagai Petunjuk Bagi Yang Bertaqwa Dalam Tafsir Jalalain Surat Al-Baqarah Ayat 1-6 - Zuman Malaka; Abdullah Isa (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
In the Al-Qur'an surah Al-Baqarah Verses 1-6 it is explained that the Al-Qur'an is a guide for pious people. This article aims to discover the Al-Qur'an as a guide for those who are pious in Jalalain's Interpretation of Surah Al-Baqarah verses 1-6. The Interpretation result of Jalalain Al-Baqarah verses 1-6 explained that the Qur'an is God's book which is a guide for those who are pious. However, contextually the guidance is not merely waiting for it to come from Allah SWT, but requires effort to get instructions from Allah SWT. In addition, there are things that can hinder getting guidance or hudan, namely disbelievers because they are closed from faith so they do not get guidance from Allah SWT.